Incursions into Territorial Waters: Violations of Innocent Passage by Foreign Autonomous Underwater Vehicles (A Case Study on Indonesia's Territorial Waters) - Anom, Surya; Citrawan, Ahmad Lanang (Yustisia Tirtayasa : Jurnal Tugas Akhir, 2024)
Based on AIS (Automatic Identication System) monitoring, some time ago some violations occurred in Indonesian waters. The violation of entering the territory of the State of Indonesia, especially in the sea area using a seaglider or AUV, was carried out by Chinese-agged ships without permission from the Government of Indonesia, such as the Xiang Yang Hong 03, Xiang Yang Hong 19, Xiang Yang Hong 01, and Yuan Wang 6. Alleged drones or AUVs that enter Indonesia's sovereign territory belong to China because the AUV ndings are written China Shenyang Institute of Automation, Chinese Academy of Sciences. The cross-peaceful violations committed by the Chinese State using the AUV were carried out many times, so the Indonesian Government has protested through the Ministry of Foreign Affairs, but until now it has not received a response from the Chinese State. The research method uses normative juridical, which analyzes the literature on primary data in the form of authoritative legal materials and secondary legal materials in the form of legal publications. This paper will use a statutory approach to see the consistency and compatibility between one law and another. Furthermore, it is analyzed using a descriptive method.